XML Data Management: Native XML and XML-Enabled Database Systems - Chaudhri, Akmal B. (Addison Wesley, 2011)
Within a very short amount of time XML has become an essential part of almost every developer's arsenal of tools. It has affected every area of software. One of the fields where the impact of XML is still being worked out is in the world of databases and data management. Will XML and native XML databases replace traditional relational databases? How can XML be used as a tool to make relational databases even stronger? This book is intended to address these questions. It provides a discusssion of the various XML data management approaches employed in a range of products and applications. The book is based on a series of presentations at last year's OOPSLA conference. Topics covered range from using XML with Oracle9i or SQL Server to embedded XML databases to Tamino. Individual chapters are written by experts in those fields. In all cases the authors use concrete, practical examples, explore alternative approaches, and examine their strengths and weaknesses. There is no other book with the breadth of coverage offered here.